Customize your Mac. IN Features. - Aguilera, Ray.; Berenstain, Adam.; Bohon, Cory.; Curthoys, Paul.; Ochs, Susie
Apple's gaer is gorgeouslyd esigned, but that shouldn't stop you from personalizing your Mac, iPhones, and iPad with beautiful tweaks that make it all yours.
Keywords: iPhone (Smartphone); iPad (Computer); Mac OS; Mac OS X